Exploring Biomedical Innovations in the Formulation and Assessment of Medicated Hard Candy Lozenges Containing Metoclopramide Hydrochloride - Sd. Riaz Hussain Chistia; N. Jyothi Reddy; H. Padma Latha; CH. Sri Divya; S. Deepa (International Journal of Biomedical Innovations and Engineering, 2024)
The objective of this study was to formulate and evaluate metoclopramide hydrochloride medicated lozenges for antiemetic action through buccal absorption by incorporating a polymer. All formulations were developed and assessed for in-vitro drug release, physical appearance, weight variation, thickness, hardness, moisture content, mouth-dissolving time, and drug content. The prepared lozenges exhibited uniformity in weight and thickness. The hardness of all formulations ranged between 7.3–15.50 kg/cm², falling within standard limits. The mouth-dissolving time varied from 7:06 to 30:28 minutes, with formulation F10 taking the longest to dissolve. The acceptable moisture content for lozenges should range from 0.5% to 1.5%, and the formulated lozenges meet this criterion. The drug content across all formulations (F1–F10) remained within the acceptable range of 90%–110%. In the in-vitro drug release study, metoclopramide hydrochloride lozenges containing methyl cellulose at concentrations of 0.75%, 0.5%, and 0.25% exhibited the highest drug release within 30 minutes, with formulation F10 achieving 100.6% release. The in-vitro release kinetic study of the optimized formulation (F10) followed a first-order release pattern, with drug release governed by diffusion, dissolution, and a non-Fickian diffusion mechanism. Based on this study, isomalt was successfully utilized as a tooth-friendly sugar substitute in medicated lozenges. Due to its low-caloric value and resistance to plaque formation, it can be safely recommended for diabetic and pediatric patients.
Keywords: Formulation Development; Hard Candy Lozenges; Metoclopramide Hydrochloride; evaluation